A review of social issues for biofuels investment in Mozambique - Emílio Tost\~ao; Giles Henley; Joel Tembe; Aristides Baloi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This study discusses the potential for expanding cultivation of biofuel feedstock in Mozambique from several angles. Taking the case of sugarcane, it explores the potential to expand production, through exploring both biophysical factors and patterns of existing investment. We review recent literature on trends in land allocation and practices of resettlement in Mozambique to highlight opportunities and constraints that current plans for biofuel production should consider. While resource availability suggest opportunities exist to expand cultivation, minimizing social risks when doing so depends on the processes followed to transfer land from existing users, and compensation in the short and long term.
Keywords: O13; Q10; 330; biofuels; Mozambique; sugarcane